Influence of chemical composition and microstructure on fatigue performance of reinforcing steel - Ro, I. -Jun; Lee, Chang-Gi; Aota, Leonardo Shoji; Choi, Woonam; Won, Sungbin; Ahn, Jae-Pyoung; Kim, Hae-Ryoung; Choi, Gwanghyo; Gault, Baptiste; Kim, Se-Ho (Elsevier Editora Ltda, 2025)
Reinforcing steels play a crucial role in ensuring structural safety, particularly in seismic areas where fatigue failure can have catastrophic consequences. In this work, we examine how microstructural and compositional characteristics influence the fatigue performance of core-shell hybrid reinforcing steels (B500B). Following fatigue testing up to five million cycles, we observed a pronounced increase in both pore size and density, most notably in the shell region, attributable to a high concentration of inclusions. High-resolution microscopy revealed the presence of voids adjacent to MnS particles, alongside nanoscale cementite precipitates and Cu clusters at the interfaces of the cementite and surrounding martensite. Furthermore, elemental partitioning of Mn, Cu, Si, Ni, and Cr led to an enrichment of carbon in the tempered martensite, rendering the shell more brittle and prone to fatigue-induced cracking. These findings highlight the necessity of precise control over alloying elements to minimize the formation of detrimental phases, thereby improving the fatigue resistance and overall durability of reinforcing steels in seismic applications.